Outracing lung signal decay: potential of ultrashort echo time MRI - Wielpütz, Mark Oliver; Triphan, Simon M. F.; Jobst, Bertram; Kauczor, Hans-Ulrich (RöFo, 2019)
Background Magnetic resonance imaging (MRI) of the pulmonary parenchyma is generally hampered by multiple challenges related to patient respiratory- and circulation-related motion, low proton density and extremely fast signal decay due to the structure of the lungs evolved for gas exchange. Methods Systematic literature database research as well as annual participation in conferences dedicated to pulmonary MRI for more than the past 20 years by at least one member of the author team. Results and Conclusion The problem of motion has been addressed in the past by developments such as triggering, gating and parallel imaging. The second problem has, in part, turned out to be an advantage in those diseases that lead to an increase in lung substance and thus an increase in signal relative to the background. To reduce signal decay, ultrashort echo time (UTE) methods were developed to minimize the time between excitation and readout. Having been postulated a while ago, improved hardware and software now open up the possibility of achieving echo times shorter than 200 µs, increasing lung signal significantly by forestalling signal decay and more effectively using the few protons available. Such UTE techniques may not only improve structural imaging of the lung but also enhance functional imaging, including ventilation and perfusion imaging as well as quantitative parameter mapping. Because of accelerating progress in this field of lung MRI, the review at hand seeks to introduce some technical properties as well as to summarize the growing data from applications in humans and disease, which promise that UTE MRI will play an important role in the morphological and functional assessment of the lung in the near future. Key Points: Citation Format
Publikationsdatum: 26. September 2018 (eFirst)
Gesehen am 15.07.2029